Nonlinear absorption spectrum in perylene derivatives - Oliveira, S. L.; De Boni, L.; Corrêa, D. S.; Misoguti, L.; Zílio, S. C.; Mendonça, C. R.; Constantino, C. J L [UNESP]; Aroca, R. F. (Institute of Electrical and Electronics Engineers (IEEE), 2005)
Knowledge about nonlinear absorption spectra of materials used in photonic devices is of paramount importance in determining their optimum operation wavelengths. In this work, we have investigated the two-photon absorption (2PA) degenerate cross-section spectrum for perylene derivatives using the Z-scan technique with femtosecond laser pulses. All perylene derivatives studied present large 2PA cross-sections, only comparable to the best ones reported in the literature. The results achieved in the present investigation indicate perylene derivatives as promising materials for two-photon applications. ©2005 Optical Society of America.
Keywords: Derivatives; Laser pulses; Light absorption; Photons; Quantum optics; Femtosecond laser pulses; Nonlinear absorption; Perylene derivatives; Two-photon absorption (2PA); Nonlinear optics